Pembuatan Alat Penyaring Air Sederhana Bagi Siswa Pondok Pesantren AS SAADAH Puri Serpong - Gadang Priyotomo; Ahsonul Anam; Wawan Budiarto (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Water for humans is of course a very important thing, moreover around 55-60 percent of the adult body weight consists of water. Therefore, we really need water for survival so that the body works optimally. Even though the earth has an abundant water content, in fact there is only about 0.3 percent that can be used by humans. the need for clean water is becoming scarce, therefore water purification becomes indispensable and becomes an alternative to the scarcity of clean water. PKM partners use well water as water for bathing, washing, watering and other purposes. Well water is pumped into the reservoir. Sometimes the well water is cloudy, so it's not comfortable when you want to use it. In simple terms, water purification functions to reduce turbidity, slightly eliminate or reduce odors, but has not been able to reduce the levels of pollutants in it to make it suitable for its final use, for example for consumption purposes such as drinking, cooking and others. The end result of using this simple water filter is water that looks clearer, making it suitable for use for bathing, washing, watering plants and other purposes.